A randomized comparison between Accuro and palpation-guided spinal anesthesia for obese patients undergoing orthopedic surgery. Issue 1 (25th October 2019) - Ghisi, Daniela; Tomasi, Marco; Giannone, Sandra; Luppi, Alessandra; Aurini, Lucia; Toccaceli, Letizia; Benazzo, Andrea; Bonarelli, Stefano
Abstract : Background: Although obese patients benefit from neuraxial anesthesia, technical difficulties often discourage its use. The current randomized trial compared Accuro, a hand-held, battery-operated ultrasound (US) device, and conventional palpation for spinal anesthesia in obese patients undergoing orthopedic surgery. We hypothesized that Accuro would decrease the number of needle redirections. Methods: We enrolled 130 men and women with a body mass index ≥30 kg/m 2, scheduled for lower limb surgery under spinal block. Patients were randomized either to the Control group (group C: spinal block after palpation of cutaneous landmarks) or to the Accuro group (group A: preprocedural US scan with Accuro to identify the needle insertion point). The procedural time, the number of skin passes and of needle redirections, the occurrence of failure and adverse events were recorded. Results: Ninety-nine patients completed the study. Patients in group Accuro showed a median (IQR) number of redirections of 3 (0–9) and a median (IQR) number of needle passes through the skin of 1 (1-2) versus 6 (1-16) and 1 (1-3), respectively, in group Control (p=0.008, p=0.019). The performance time was 558±232 s in group Accuro versus 348±255 s in group Control (p<0.001). There were no intergroup differences in terms of failed blocks and adverse events. Conclusions: The use of Accuro reduced the number of needle redirections and passes through the skin when performing spinal anesthesia, but required a longer procedural time. Trial registration number: ClinicalTrials.gov registry (NCT03075488 ).